Neuro-modulation, aminergic neuro-disinhibition and neuro-degeneration: draft of a comprehensive theory for Alzheimer disease - Schmitt, Horst Peter (Medical hypotheses, 2005)
Summary: A comprehensive theory for Alzheimer disease (AD) which can provide a clue to the neuronal selective vulnerability (pathoklisis) is still missing. Based upon evidence from the current literature, the present work is aimed at proposing such a theory, namely the ‘aminergic disinhibition theory’ of AD. It includes data-based hypotheses as to the pathoklisis, mechanisms of neuro-degeneration and dementia as well as the aetiology of the disease. Alzheimer disease is regarded as a disorder of neural input modulation caused by the degeneration of four modulatory amine transmitter (MAT) systems, namely the serotoninergic, the noradrenergic, the histaminergic, and the cholinergic systems with ascending projections. MATs modulate cognitive processing including arousal, attention, and synaptic plasticity in learning and memory, not only through direct, mostly inhibitory impact on principal neurones but also partially through interaction with local networks of GABA-ergic inter-neurones. The distribution and magnitude of the pathology in AD roughly correlate with the distribution and magnitude of MAT modulation: Regions more densely innervated by ascending MAT projections are, as a rule, more severely affected than areas receiving less MAT innervation. Because the global effect of MATs in the forebrain is inhibition, the degeneration of four MAT systems, some related peptidergic systems and a secondary alleviation of the GABA-ergic transmission means a fundamental loss of inhibitory impact in the neuronal circuitry resulting in neuronal (aminergic) disinhibition. Clearly, the basic mechanism promoting neuronal death in AD is thought to be a chronic disturbance of the inhibition-excitation balance to the advantage of excitation. Chronic over-excitation is conceived to result in Ca2+ dependent cellular excito-toxicity leading to neuro-degeneration including amyloid-β production and NFT formation. Disinhibited neurons will degenerate while less excited (relatively over-inhibited) neurones will survive. Because the decline of aminergic transmission in AD is likely to start at the receptor level, it is hypothesized that early impairment by a molecular ‘hit’ to an MAT receptor (or a group of receptors) initiates a pathogenetic cascade that develops in an avalanche-like manner. Based on experimental evidence from the literature, the ‘hit’ might be the attachment of a targeted pathogen like a small roaming amino acid sequence to the receptor(s), e.g., the serotoninergic 5-HT2A-R. Referential sequence analysis could be a means to identify such a small pathogen hidden in a large receptor molecule.